A novel colorimetric indicator based on agar incorporated with Arnebia euchroma root extracts for monitoring fish freshness. (May 2019) - Huang, Shaoyun; Xiong, Yabo; Zou, Yang; Dong, Qingfeng; Ding, Fuyuan; Liu, Xinghai; Li, Houbin
Abstract: This work aimed to develop and characterize a novel indicator film for monitoring fish freshness based on agar incorporated with natural dye extracted from Arnebia euchroma root (AEREs). The Fourier transform infrared spectroscopy results reflected that some new interactions have occurred between polymer matrix and natural dye. And the results of X-ray diffraction and scanning electron microscopy indicated that AEREs were well dispersed in the agar base film. A certain decrease was observed in water solubility, swelling ratio and elongation at break of colorimetric film but tensile strength, Young's modulus, water vapor permeability and water contact angle of colorimetric film were increased by addition of AEREs. The prepared indicator films were used as freshness labels in an application trial, which was conducted to monitor the freshness of Wuchang bream ( Megalobrama amblycephala ) under refrigeration (4 °C) and at room temperature (25 °C). The total volatile basic nitrogen (TVB-N) and total viable count (TVC) of fish sample were determined periodically, and the color change of freshness labels was recorded simultaneously. The results showed that the indicator film with lower content of AEREs demonstrated more conspicuous color change during fish spoilage. And the color response of freshness label was consistent with the spoilage threshold of TVC and TVB-N content in fish sample. Thus, these colorimetric indicator films could indicate the fish spoilage by visible color change. The developed colorimetric indicator film is expected to provide a convenient, non-destructive and visual method to estimate fish freshness during storage. Graphical abstract: Image 1 Highlights: A novel colorimetric film based on polysaccharide was successfully developed. The extract of Chinese herbal medicine was used as pH sensing dye in this system. The colorimetric film with lower content of dye has better color response. The developed colorimetric film is expected to apply in fish spoilage monitoring.